THE CONCEPTOSPHERE OF DIVINE LANGUAGE IN ENGLISH LINGUACULTURE - Nasrullayeva Mohigul Suhrobovna (Research Parks Publishing LLC, 2020)
This article takes into consideration the specific issue of divinity and religion in the English language from both linguistic and linguacultural point of view including some authentic examples on it and additionally investigates the distinctive intercourse between language and culture